PERSEPSI PENGGUNA TERHADAP ANGKUTAN ONLINE DI KOTA BANDUNG - Oktaviani Riandiatmi; Tri Basuki Joewono (Jurnal Transportasi, 2018)
Abstract An impact of the advancement of information and communication technology is the emergence of transportation that relies on technology-based applications as a link between providers and users of transportation services, known as online transportation. There are many factors that determine a user's decision to choose an online transportation provider. These factors are based on the user's perception of experience when using the service. This study aims to analyze the perceptions of users that influence the selection of 4 providers of application-based transportation services in the City of Bandung, namely Go-Jek, Uber, Grab, and My Blue Bird, and the interrelationships between perceptions given. The results of this study indicate that the assessments given by respondents to online transportation service providers are approxi-mately equal, because there is no significant difference in assessment among different online transportation providers. Keywords: online transportation, transportation service providers, user’s perceptions, transportation service users  Abstrak Suatu dampak adanya kemajuan teknologi informasi dan komunikasi adalah munculnya transportasi yang mengandalkan aplikasi berbasis teknologi sebagai penghubung antara penyedia dan pengguna jasa transportasi, yang dikenal sebagai transportasi online. Ada banyak faktor yang menentukan keputusan pengguna untuk memilih penyedia transportasi online. Faktor-faktor penentu tersebut didasarkan pada persepsi pengguna terhadap pengalaman saat menggunakan layanan tersebut. Penelitian ini bertujuan untuk menganalisis persepsi pengguna yang memengaruhi pemilihan 4 penyedia jasa transportasi berbasis aplikasi di Kota Bandung, yaitu Go-Jek, Uber, Grab, dan My Blue Bird, serta keterkaitan antarpersepsi yang diberikan. Hasil penelitian ini menunjukkan bahwa penilaian yang diberikan oleh responden kepada penyedia jasa transportasi online kurang lebih seimbang, karena tidak ada perbedaan penilaian yang mencolok di antara penyedia transportasi online yang berbeda-beda. Kata-kata kunci: transportasi online, penyedia jasa transportasi, persepsi pengguna, pengguna jasa transportasi